(untitled) (Bangladesh Journal of Medical Biochemistry, 2015)
The study was conducted to evaluate the effects of fasting for a period of one month during Ramadan on the lipid profile of Bangladeshi female volunteers who fasted during the Arabic month of Ramadan, when there occurs a change, both in the pattern and timing of dietary intake. Findings of the study showed that Ramadan fast significantly reduced serum Total cholesterol (TC) (p=0.030) and Low density lipoprotein (LDL-C) (p=0.011). A statistically nonsignificant elevation of triglyceride (TG)) was observed (p=0.598). High density lipoprotein cholesterol (HDL-C) also found to be raised significantly at the end of fasting (p = 0.037). Findings of the study revealed that fasting during the month of Ramadan changes lipid profile pattern in an aniatherogenic direction and may be beneficial to health. DOI: http://dx.doi.org/10.3329/bjmb.v7i2.22412 Bangladesh J Med Biochem 2014; 7(2): 47-51